Legal bases of labor migration in Central Asia - Saidov Azambek Rayimjon o`g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the countries of Central Asia in the years of independence, the emergence of migration processes, their legal basis and integration with world labor legislation.